THEORETICAL BASIS OF APPLICATION OF STEM CELLS TRANSPLANTATION IN CLINICAL PRACTICE - Дерпак, Юрій (SWorldJournal, 2025)
A total of 58 blood donors were examined (32 men and 26 women): 27 active donors (16 men and 11 women) who give blood regularly, at least 3 times a year and 31 primary donors (16 men and 15 women) who donate blood the first time.For all examined donors w